Capsicum annuum proteinase inhibitor ingestion negatively impacts the growth of sorghum pest Chilo partellus and promotes differential protease expression - Jadhav, A. R.; War, A. R.; Nikam, A. N.; Adhav, A. S.; Gupta, V. S.; Sharma, H. C.; Giri, A. P.; Tamhane, V.A. (Biochemistry and Biophysics Reports, 2016)
Background Chilo partellus is an important insect pest infesting sorghum and maize. The larvae internalize in the stem, rendering difficulties in pest management. We investigated the effects of Capsicum annuum proteinase inhibitors (CanPIs) on C. partellus larvae by in-vitro and in-vivo experiments. Methods Recombinant CanPI-7 (with four-Inhibitory Repeat Domains, IRDs), -22 (two-IRDs) and insect proteinase activities were estimated by proteinase assays, dot blot assays and in gel activity assays. Feeding bioassays of lab reared C. partellus with CanPI-7 and -22 were performed. C. partellus proteinase gene expression was done by RT-PCR. In-silico structure prediction of proteinases and CanPI IRDs was carried out, their validation and molecular docking was done for estimating the interaction strength. Results Larval proteinases of C. partellus showed higher activity at alkaline pH and expressed few proteinase isoforms. Both CanPIs showed strong inhibition of C. partellus larval proteinases. Feeding bioassays of C. partellus with CanPIs revealed a dose dependent retardation of larval growth, reduction of pupal mass and fecundity, while larval and pupal periods increased significantly. Ingestion of CanPIs resulted in differential up-regulation of C. partellus proteinase isoforms, which were sensitive to CanPI-7 but were insensitive to CanPI-22. In-silico interaction studies indicated the strong interaction of IRD-9 (of CanPI-22) with Chilo proteinases tested. Conclusions Of the two PIs tested, CanPI-7 prevents induction of inhibitor insensitive proteinases in C. partellus so it can be explored for developing C. partellus tolerance in sorghum. General significance Ingestion of CanPIs, effectively retards C. partellus growth; while differentially regulating the proteinases.

Data of in vitro synthesized dsRNAs on growth and development of helicoverpa armigera - Chikate, Y. R.; Dawkar, V. V.; Barbole, R. S.; Tilak, P. V.; Gupta, V. S.; Giri, A. P. (Data in Brief, 2016)
The data presented in this article is related to the research article "RNAi of selected candidate genes interrupts growth and development of Helicoverpa armigera" (Chikate et al., 2016) [1]. RNA interference (RNAi) is emerging as a potent insect pest control strategy over current methods and their resistance by pest. In this study we tested 15 different in vitro synthesized dsRNAs for gene silencing in Helicoverpa armigera. These dsRNAs were specific against H. armigera enzymes/proteins such as proteases like trypsins (HaTry2, 3, 4 and 6), chymotrypsin (HaChy4) and cysteine proteases such as cathepsin (HaCATHL); glutathione S-transferases (HaGST1a, 6 and 8); esterases (HaAce4, HaJHE); catalase (HaCAT); super-oxide-dismutase (HaCu/ZnSOD); fatty acid binding protein (HaFabp) and chitin deacetylase (HaCda5b). These dsRNAs were fed to second instar larvae at an optimized dose (60 μg/day) for 3 days separately. Effects of dsRNA feeding were observed in terms of larval mass gain, percentage mortality and phenotypic abnormalities in later developmental stages of H. armigera. These findings might provide potential new candidates for designing sequence-specific dsRNA as pesticide in crop protection.

Data on changes in the fatty acid composition during fruit development and ripening of three mango cultivars (Alphonso, Pairi and Kent) varying in lactone content - Deshpande, A. B.; Chidley, H. G.; Oak, P. S.; Pujari, K. H.; Giri, A. P.; Gupta, V. S. (Data in Brief, 2016)
Data in this article presents fatty acid composition of three mango cultivars; Alphonso, Pairi and Kent through fruit development and ripening. Change in the ω-6 and ω-3 fatty acids level during mango fruit development and ripening is depicted. Also, data on aroma volatile ‘lactones’ composition from pulp and skin tissues of these cultivars at their ripe stage, respectively is provided. Statistical data is also shown, which correlates modulation in lactone content with that of fatty acid composition and content during fruit development and ripening in all the three mango cultivars.

Diversity of arsenic resistant bacteria from Lonar lake: A meteorite impact alkaline crater lake in Indi - Bagade, A. V.; Paul, D.; Rikame, T.; Giri, A. P.; Dhotre, D.; Pawar, S.; Kodam, K. (Arsenic Research and Global Sustainability - Proceedings of the 6th International Congress on Arsenic in the Environment, AS 2016, 2016)
Lonar lake known for its meteorite impact origin and highly alkaline environment harbors a plethora of diverse organisms. Arsenic transforming microbe diversity from Lonar remains unexplored. We attempted to explore the microorganisms causing arsenic transformation using culture-dependent and independent approaches. Amongst the 67 microbes isolated, Bacillus infantis L4-18 and Bacillus solimangrovi L4-7b could oxidise 15 mM arsenite in 8 days. None of the cultures could reduce arsenate. All the other isolates resisted 2 mM arsenic. In the culture independent approach, microbial diversity revealed Bacteroides (41.9%), followed by Proteobacteria (17.9%), Firmicutes (14.2%), Actinobacteria (13.9%), occurring in the Lonar sediment sample. This study provides foundation to study microbial arsenic biogeochemical cycle along with other biochemical cycles and microbial function in Lonar lake eco system.

Plant cholesterol biosynthetic pathway overlaps with phytosterol metabolism - Sonawane, P. D.; Pollier, J.; Panda, S.; Szymanski, J.; Massalha, H.; Yona, M.; Unger, T.; Malitsky, S.; Arendt, P.; Pauwels, L.; Almekias-Siegl, E.; Rogachev, I.; et al. (Nature Plants, 2017)
The amount of cholesterol made by many plants is not negligible. Whereas cholesterogenesis in animals was elucidated decades ago, the plant pathway has remained enigmatic. Among other roles, cholesterol is a key precursor for thousands of bioactive plant metabolites, including the well-known Solanum steroidal glycoalkaloids. Integrating tomato transcript and protein co-expression data revealed candidate genes putatively associated with cholesterol biosynthesis. A combination of functional assays including gene silencing, examination of recombinant enzyme activity and yeast mutant complementation suggests the cholesterol pathway comprises 12 enzymes acting in 10 steps. It appears that half of the cholesterogenesis-specific enzymes evolved through gene duplication and divergence from phytosterol biosynthetic enzymes, whereas others act reciprocally in both cholesterol and phytosterol metabolism. Our findings provide a unique example of nature's capacity to exploit existing protein folds and catalytic machineries from primary metabolism to assemble a new, multi-step metabolic pathway. Finally, the engineering of a 'high-cholesterol' model plant underscores the future value of our gene toolbox to produce high-value steroidal compounds via synthetic biology.

Data on metabolic profiling of spongy tissue disorder in Mangifera indica cv. Alphonso - Oak, P. S.; Deshpande, A. B.; Pujari, K. H.; Prabhudesai, S. S.; Giri, A. P.; Gupta, V. S. (Data in Brief, 2019)
Data in this article presents aroma volatiles and fatty acids composition of mesocarp specific malady namely spongy tissue disorder in Mangifera indica cv. Alphonso. Quantitative changes in various aroma volatile compound classes as well as saturated and unsaturated fatty acids in spongy tissue vis-à-vis healthy mesocarp have been analyzed throughout the development of the disorder. Statistical data analysis correlates the dynamic changes in the aroma volatiles composition to that of the modulation in the fatty acids profile.

Protein α-amylase inhibitor from withania somnifera and its role in overall quality and nutritional value improvement of potato chips during processing - Kasar, S. S.; Giri, A. P.; Pawar, P. K.; Maheshwari, V. L. (Food and Bioprocess Technology, 2019)
Cold storage and processing increase the reducing sugar level in potato (Solanum tuberosum L.) which is responsible for browning and acrylamide formation that adversely affect sensory and nutrient quality of chips. Effect of α-amylase inhibitor from Withania somnifera (WSAI) treatment on the overall quality improvement of potato chips during processing was studied. WSAI treatment to potato slices at 200 ppm for 30 min was found to reduce browning (60%), residual amylase, and polyphenol oxidase activities (~ 40%) and reduce sugar level by 25%, respectively, over control. Color match analysis indicated an improvement in whiteness and brightness indices and a significant reduction in yellowness index of potato chips. The treatment proved to be superior over blanching and reduction in acrylamide generation during frying was which also observed in chips treated with it. Furthermore, our results were comparable to that of treatment with α-amylase inhibitor of Triticum aestivum and better than synthetic inhibitor, acarbose.
Keywords: Acrylamide; alpha-amylase inhibitor; Browning of potato; Reducing sugars; Sensory and nutrient quality